2011
DOI: 10.1097/icl.0b013e3181f91f2f
|View full text |Cite
|
Sign up to set email alerts
|

Severity and Determinants of Pinguecula in a Hospital-Based Population

Abstract: This was the first assessment of the grade of pinguecula in a large series of patients. Our findings strongly suggest that pinguecula is an age-dependent lesion that occurs from young adulthood onward. The present grading system should also be useful for future clinical studies of pinguecula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Pinguecula has been reported to be associated with aging. [1][2][3][4][5][6][7] Development of pinguecula may also be influenced by various other factors, such as UV light, 3,5,8 increased cholesterol levels, 9 elastotic degeneration, 10 dry eyes, 11 and wearing contact lenses. 12 Although only a few studies of conjunctival structural changes have been conducted in patients with pinguecula, it has been suggested that elastotic degeneration of the collagen in the substantia propria may be involved in the onset of this condition.…”
mentioning
confidence: 99%
“…Pinguecula has been reported to be associated with aging. [1][2][3][4][5][6][7] Development of pinguecula may also be influenced by various other factors, such as UV light, 3,5,8 increased cholesterol levels, 9 elastotic degeneration, 10 dry eyes, 11 and wearing contact lenses. 12 Although only a few studies of conjunctival structural changes have been conducted in patients with pinguecula, it has been suggested that elastotic degeneration of the collagen in the substantia propria may be involved in the onset of this condition.…”
mentioning
confidence: 99%
“…Previous study based grading on size rather vascularization, 8 Mimura et al 8 graded pinguecula mainly based on size as follows: grade P (0)¼none, grade P (1)¼mild or moderate pinguecula (yellowish white and flat or slightly elevated lesion with a maximum diameter of ,5 mm), and grade P (2)¼severe pinguecula (vascular and elevated lesion or large pinguecula with a diameter of 5 mm or larger). In this study, we graded pingueculae within a restricted size range (2·2 to 3·3 mm) based on degree of vascularization, so direct comparison was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…There are many methods presented in the literature to grade pingueculae according to size, elevation, color, and vascularization. 8,9 Here, we focus on level of vascularization and related cosmesis as outcome measures at 12 months postoperatively.…”
mentioning
confidence: 99%
“…Понастоящем повечето публикации са базирани на конюнктивална автофлуоресценция и осигуряват солидни доказателства, че има значително УВ увреждане на междупалпебралната конюнктива (8)(9)(10). Повърхностни заболявания като пингвекула и птеригиум също са свързвани със слънчево увреждане, но е интересен фактът, че птеригиумът е по-често назален (преобладаване около 7.3%), а пингвекулата засяга почти еднакво назалната и темпоралната конюнктива с преобладаване (независимо в кое око или място) до 69.5% (11,12). В момента слънчевите очила представляват найпопулярната защита на очите от слънчеви увреждания и ултравиолетовите лъчи в частност.…”
Section: Microstructural Analysis Of the Effects Of Sunlight On The Aunclassified